WOOD AND CHARCOAL IDENTIFICATION OF SAMPLES FROM THE CAPE KRUSENSTERN BEACH RIDGE SITE COMPLEX, NORTHWEST ALASKA - Puseman, Kathryn (PaleoResearch Institute) (the Digital Archaeological Record)
A total of 54 charcoal and wood samples from the Cape Krusenstern beach ridge archaeological site complex were submitted for identification. This site complex is located within Cape Krusenstern National Monument in Northwest Alaska. Charcoal was examined in order to identify the types of wood available to and used by the prehistoric occupants of this site complex, as well as to provide identifications for charcoal samples submitted for radiocarbon dating.